Demonstration by Freeze-Etching of a Single Cleavage Plane in the Cell Wall of a Gram-Negative Bacterium - DeVoe, I. W. (1971)
In the examination of protoplasts of a gram-negative bacterium classified as a Pseudomonas sp. by freeze-etching, we found a smooth external surface which is not seen if the preparations are not “etched.” This external structure is seen as a sleeve surrounding and connecting the cells in unetched preparations, and we present evidence that it is a eutectic formed during the freezing of the specimen. In the system used in this study, the four layers of the cell wall of a gram-negative bacterium can be removed from the cell. The single cell wall cleavage plane is not affected by the removal of the loosely bound outer layer or of the peptidoglycan layer, but it is lost when the outer double track layer and the underlying soluble layer are simultaneously removed. Thus, we conclude that it is one of these two layers which is responsible for the cleavage plane which exposes variable areas of a smooth surface in the cell wall. This cell wall cleavage plane is more likely to deflect the actual cleavage of the frozen cell when cells are relatively old or when they are suspended in sucrose.